Normal percentile reference curves for skin ultrasound thickness and stiffness at Rodnan sites. Issue 2 (2nd November 2022) - Santiago, Tânia; Santos, Eduardo José Ferreira; Luis, Mariana; Gaspar, Catarina; Lima, João; Caramelo, Francisco; da Silva, Jose Antonio Pereira
Abstract : Objectives: Our primary objective was to establish preliminary normal reference curves for ultrasound–dermal thickness and skin stiffness in the 17 Rodnan skin sites, considering the effect of gender and age on these measures. As an exploratory objective, we investigated the effect of body mass index and the menopause on skin ultrasound measures. Methods: A cross-sectional study was conducted involving 140 healthy volunteers, aged 20–79 years. Recruitment was stratified by gender and age (10-year categories). Ultrasound–dermal thickness and skin stiffness were assessed by high-frequency ultrasound and shear-wave elastography, respectively, at the 17 Rodnan skin sites. Outcomes were evaluated through a mixed linear model, univariate and multivariate regressions. Normal reference curves were derived for both ultrasound measures in each skin site. An online calculator of the percentiles of skin ultrasound measures was developed. Results: Ultrasound–dermal thickness and stiffness measures were higher in men than women in all Rodnan skin sites (except in chest for ultrasound–dermal thickness). Age had also a significant impact in both ultrasound measures, but only in some skin sites. Gender and age percentile curves (97.5th, 95th, 75th, 50th, 25th, 5th, 2.5th) were plotted for each of the measures in each skin site. Conclusions: Gender and age are strongly associated with skin ultrasound parameters, imposing the need for gender-specific and age-specific reference values. Normal reference percentile curves are provided as a basis for future cooperative work to strengthen its evidence basis, representativeness and refinement regarding potentially influential factors.